Serotonin regulates mouse cranial neural crest migration. - Moiseiwitsch, J R (1995)
Serotonergic agents (uptake inhibitors, receptor ligands) cause significant craniofacial malformations in cultured mouse embryos suggesting that 5-hydroxytryptamine (serotonin) (5-HT) may be an important regulator of craniofacial development. To determine whether serotonergic regulation of cell migration might underly some of these effects, cranial neural crest (NC) explants from embryonic day 9 (E9) (plug day = E1) mouse embryos or dissociated mandibular mesenchyme cells (derived from NC) from E12 embryos were placed in a modified Boyden chamber to measure effects of serotonergic agents on cell migration. A dose-dependent effect of 5-HT on the migration of highly motile cranial NC cells was demonstrated, such that low concentrations of 5-HT stimulated migration, whereas this effect was progressively lost as the dose of 5-HT was increased. In contrast, most concentrations of 5-HT inhibited migration of less motile, mandibular mesenchyme cells. To investigate the possible involvement of specific 5-HT receptors in the stimulation of NC migration, several 5-HT subtype-selective antagonists were used to block the effects of the most stimulatory dose of 5-HT (0.01 microM). Only NAN-190 (a 5-HT1A antagonist) inhibited the effect of 5-HT, suggesting involvement of this receptor. Further evidence was obtained by using immunohistochemistry with 5-HT receptor antibodies, which revealed expression of the 5-HT1A receptor but not other subtypes by migrating NC cells in both embryos and cranial NC explants. These results suggest that by activating appropriate receptors 5-HT may regulate migration of cranial NC cells and their mesenchymal derivatives in the mouse embryo.